PENGARUH TARIF, JAM KERJA DAN JUMLAH ORDERAN TERHADAP PENDAPATAN DRIVER GO-JEK DI KOTA BANJARMASIN - ANGGIT SEPTIAWAN HARTADI; RUSDIANSYAH RUSDIANSYAH (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research was conducted to (1) analyze the effect of tariffs, working hours, and the number of orders on the revenue of GO-JEK drivers in Banjarmasin City; (2)  find out which factors predominantly influence the revenue of GO-JEK drivers in Banjarmasin City. The results of this study indicate that tariffs and the number of orders individually (partially) and jointly (simultaneously) have a positive and significant effect on the revenue of GO-JEK drivers in Banjarmasin City, while working hours have a negative and insignificant effect on the revenue of GO-JEK drivers in Banjarmasin City. The most dominant factor influencing GO-JEK driver revenue is tariff. Keywords : Tariff, Working Hours, Order Amount, Income of  GO-JEK Drivers